Judge Consideration of Marriage Dispensation at Sidenreng Rappang Religious Court - Sufri, Melda; Said, Zainal; Rauf, Aris (Al-Iftah: Journal of Islamic studies and society, 2020)
This study explains that applications for marriage dispensation at the Sidenreng Rappang Religious Court have increased from year to year, and in 2019 there were 222 cases. The purpose of this study is to describe the development of the marriage dispensation, analyze the reasons behind the application for a marriage dispensation, and reveal the judges' considerations regarding the intent of the Marriage Law in Article 7 paragraph 2 of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning marriage. This type of research is descriptive qualitative, the research location is at the Sidenreng Rappang Religious Court, for primary data sources, namely copies of decisions, marriage laws, judges, clerks and justice seeking societies and secondary data sources. The results of this study indicate that 1) Marriage dispensation at the Sidenreng Rappang Religious Court, from year to year always increases and in 2019 experienced a very sharp increase; 2) Based on cultural, educational, economic, environmental factors and pregnancy outside of marriage, and 3) Juridical analysis of the legal considerations of the Sidenreng Rappang Religious Court judge regarding the marriage dispensation Law Number 16 of 2019 and based on the rules of fiqhi and maqashid al-Syariah, the reality ignores several administrative requirements that can support judges' considerations to realize and guarantee the best interests of children.